TALAK QOBLA DUKHUL PERSPEKTIF IMAM ABU HANIFAH DAN IMAM SYAFI’I (STUDI TEKS KITAB FIQH ALA MADZAHIB AL ARBA’AH) - Rizka Maulidiyanti; ibnu Jazari; Ach. Faisol (Jurnal Hikmatina, 2022)
Marriage is an inner and outer bond that is woven by a man and woman as husband and wife to reach the pleasure of Allah SWT. To achieve it affection, love, good two-way communication and attention are needed so these things minimize the divorce occurrence. Among the types of divorce is divorce qobla dukhul, which means a divorce that occurs between a husband and wife have not had sexual relations. This divorce resulted a different law from the divorce of ba'da dukhul, therefore the author is interested in researching more deeply, especially regarding the maintenance and the period of iddah for women who are divorced in qobla dukhul state. This study uses literature review research, by conducting a study of library sources which in this case is centered on text study of the book of Abdurrahman al Jaziri namely fiqh ala madzahibil arba'ah. The result of this literature review  is that Imam Syafi'i and Imam Abu Hanifah both do not require a living for a divorced wife in qobla dukhul state. Imam Shafi'i’s opinion is that a divorced wife in qobla dukhul state is not entitled to undergo the iddah whether she had khalwat with her husband or not. Imam Abu Hanifah's opinion is that a wife who is in khalwat with her husband has to undergo iddah and a divorced wife in qobla dukhul state who had not khalwat with her husband is not entitled to undergo iddah